INTERNATIONAL RELATIONS DEVELOPMENT IN CYBERSPACE - Poda, Tatiana (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2022)
The author defines the cyberspace as a new dimension of political space and as a field of political interaction and confrontation of various political actors. The differences between cyberspace and the Internet-space are analyzed. It is shown that modern society is becoming specifically networked and digital, the relations in machine-mediated social and media net-works complement or replace communications based on the face to face interaction of political actors.